Evaluation of Significant Endoscopic Findings Using Alarm Features of Dyspepsia in Patients Visiting Gastroenterology Department at RIHS Islamabad - Hina Andaleeb, Anum Umar, Anwar Hussain Abbasi, Aleena Shahid, Khawaja Ashfaq Ahmed, Nadeem Yousuf, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to analyze significant findings of upper gastrointestinal endoscopy in patients having alarming features of dyspepsia. Study Design: Retrospective study Methodology: This retrospective study was conducted in the Gastroenterology Department at RIHS Islamabad from March 2021 to March 2022 and included adult patients presenting with alarm features and were referred for gastroscopy for dyspepsia. Those ageing below 18 years were excluded. The information including demographic data, referral for the procedure, endoscopic findings and present alarm features and dyspeptic symptoms was recorded. The diagnosis was made on the basis of visual examination. Results: A total of 140 patients who underwent gastroscopic procedures were included in the study. Most of the subjects (74.1%) reported epigastric burning, 10.8% complained of heartburn, 10.8% of regurgitation and 8% reported globus. Few of the participants reported symptoms such as bloating (5.3%), burping (5.3%), abdominal fullness (3.8%), chest pain (3.8%) and early satiety (0.8%). No significant relation was observed between warning signs and findings from the endoscopy. Conclusion: Dyspeptic patients showing alarming signs such as vomiting, dysphagia and upper gastrointestinal bleeding must be prescribed immediate endoscopy.